A TRAVEL - TIME - BASED METHOD OF MEASUREMENT OF PASSENGER CAR EQUIVALENTS OF HEAVY VEHICLES ON GRADES - Tejokusumo Joyosugito, Ahmad
Heavy Vehicles (HVs), reduce the quality of traffic flow in terms of total vehicles per-hour. In effect, each HV displaces several passenger cars in the flow. The number of passenger cars that each HV represents under specific conditions is termed the passenger car equivalent (PCE) for those conditions. Because there is no agreement on how to measure the PCE of HVs and what is the most effective measure of PCE in an unforced mixed traffic flow (low volume) at two-lane two-way upgrade rural highways, the present research attempted to develop a method of measuring PCE values for these conditions. that HVs cause delay to light vehicles (LVs), this led to travel time being used as the most effective measure of PCE. The basic definition of PCE used was: The ratio between the observed travel time of LVs impeded by a HV in a platoon and their expected travel time (TR), where T is the travel time that would be experienced by the LVs in a basic stream (a traffic stream consisting only of LVs) and having the same level of service (LOS) as that of a mixed traffic stream. For a mixed traffic stream, the final formula developed was based on this definition, after considering the traffic stream composition and the relationships between the trajectories of successive vehicles climbing the grade. In determining T , a method for quantifying LOS was also developed which was based on the assumption that the cumulative leading headway relative frequency distribution function from a traffic stream represents a particular LOS. Upper bound and lower bound approximations were introduced in order to place confidence limits about the PCE values. The measurement method was examined using data from two short and steep upgrades in West Java. It was also necessary to develop a hypothetical data set at one location which simulated conditions with no overtaking. Applying the method it was found that the PCE values based on the travel time ratio had a range of 1.0 to 1.1 where no overtaking occurred at one site and 1.1 to 1.3 at the other where overtaking did occur. The range for the hypothetical data (with no overtaking) was 1.2 to 2.1. The research shows that its possible to develop an empirical method for measuring PCE values, but that certain refinements are still required.